Art in an age of civil struggle, 1848-1871 - Boime, Albert (Boime, Albert. Social history of modern art, 2007)
From the European revolutions of 1848 through the Italian independence movement, the American Civil War, and the French Commune, the era Albert Boime explores in this fourth volume of his epic series was, in a word, transformative. The period, which gave rise to such luminaries as Karl Marx and Charles Darwin, was also characterized by civic upheaval, quantum leaps in science and technology, and the increasing secularization of intellectual pursuits and ordinary life. In a sweeping narrative that adds critical depth to a key epoch in modern art?s history, Art in an Age of Civil Struggle shows.